2008
DOI: 10.1002/pd.2007
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal management and long‐term outcome for survivors with congenital diaphragmatic hernia

Abstract: Significant advances in the postnatal management of patients with congenital diaphragmatic hernia (CDH) have resulted in a remarkable improvement in survival rates over the past two decades. The success of current postnatal management of CDH patients has rendered fetal intervention to be limited to the most severe cases, and the role for prenatal treatment of CDH patients remains unclear. The adoption of lung-preserving strategies including high-frequency oscillatory ventilation (HFOV) and extracorporeal membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 127 publications
1
65
0
3
Order By: Relevance
“…Significant advances in the post-natal management of patients with CDH have resulted in improved survival rates over the past two decades [46]. Nevertheless, most series still reported overall post-natal survival in isolated CDH around 60-70%, although some survival rates of .90% have recently been reported [83,84].…”
Section: Long-term Prognosis Of Cdh Infancymentioning
confidence: 99%
See 1 more Smart Citation
“…Significant advances in the post-natal management of patients with CDH have resulted in improved survival rates over the past two decades [46]. Nevertheless, most series still reported overall post-natal survival in isolated CDH around 60-70%, although some survival rates of .90% have recently been reported [83,84].…”
Section: Long-term Prognosis Of Cdh Infancymentioning
confidence: 99%
“…These patients have a high incidence of respiratory, nutritional, musculoskeletal, neurological and gastrointestinal morbidities [46,[90][91][92]. Furthermore, the recent improved survival of very sick babies is associated with increased, particularly pulmonary, morbidity among survivors [2,46] persisting beyond the initial hospitalisation, especially in those treated with ECMO [93,94]. SPOEL et al [95] recently observed that mean maximal expiratory flows at functional residual capacity (FRC) were significantly lower than predicted values at 6 and 12 months of age in CDH survivors.…”
Section: Long-term Prognosis Of Cdh Infancymentioning
confidence: 99%
“…[5][6][7]13,19,20 These conditions may require frequent hospital and subspecialty care. 21,22 Trends in the incidence of and mortality from many specific conditions that would contribute to medical complexity (eg, CP, chronic lung disease, mental retardation, hydrocephalus, and congenital birth defects) show the occurrence of these individual conditions to be fairly stable over the recent past. [5][6][7]12,13,[23][24][25][26] On the other hand, some disorders have certainly increased in frequency.…”
mentioning
confidence: 99%
“…In those who come to surgery the prognosis is generally good with at least 80% survival. 3,4,5 In general the surgery for bowel atresia is relatively straightforward with an anastomosis of proximal to distal bowel tailored depending on the size difference. Complications include delay in feeding with a dilated floppy proximal bowel segment, thus if possible the very dilated proximal segment in small bowel atresia should be excised or trimmed 6 .…”
Section: Congenital Diaphragmatic Herniamentioning
confidence: 99%